A modern management model for patients with acute and subacute psychiatric problems in the emergency department of Trento (Northern Italy) - Mjriam Sano'; Michela Marchiori; Wilma Angela Renata Di Napoli (Emergency Care Journal)
In Italy, over 86% of patients with mental disorders have one emergency department visit per year, with 6–9% having two visits and approximately 2% having three visits. It is not significant to include those with four or more visits in this data set. In the context of the COVID-19 pandemic, there has been a notable increase in the utilisation of emergency services for psychiatric concerns. In our emergency department (ED), we observed a 10% increase in admissions for psychiatric problems, psychomotor agitation, behavioural disorders, and drug intoxication between 2022 and 2023. We present an organisational management model that has been found to be effective for patients with minor psychiatric problems, those who repeatedly present to the emergency department, and/or those with discontinuous referrals to the relevant mental health centre or acute episodes. One possible strategy could be to consider directing psychiatric emergencies that can be deferred to territorial crisis management from the Trento emergency department to the mental health centre.